Framing the future for taxonomic monography: Improving recognition, support, and access - Gorneau Jacob A.; Ausich William I.; Bertolino Sandro; Bik Holly; Daly Marymegan; Demissew Sebsebe; Donoso David A.; Folk Ryan; Freire-Fierro Alina; Ghazanfar Shahina A.; Grace Olwen M.; Hu Ai-Qun; et al. (The Ohio State University Libraries, 2022)
Taxonomic monographs synthesize biodiversity knowledge and document biodiversity change through recent and geological time for a particular organismal group, sometimes also incorporating cultural and place-based knowledge. They are a vehicle through which broader questions about ecological and evolutionary patterns and processes can be generated and answered (e.g., Muñoz Rodríguez et al., 2019). Chiefly, monography represents the foundational research upon which all biological work is based (Hamilton et al., 2021). Moreover, monography can be a pathway to developing inclusive scientific practices, engaging diverse audiences in expanding and disseminating indigenous and local knowledge and significance of place. Apart from the scientific importance of monography, these comprehensive biodiversity treatments are also crucial for policy, conservation, human wellbeing, and the sustainable use of natural resources. Taxonomic, cultural and biodiversity data within monographs aid in the implementation of law and policy, such as the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES), the Nagoya Protocol of the Convention on Biological Diversity (Buck & Hamilton, 2011), and the International Union for Conservation of Nature (IUCN) Red List (e.g., Neo et al., 2017). While vital as a knowledge resource and tool for conservation and research, monographs are not available for many groups of organisms. This is of particular concern for organisms that are threatened with extinction, of medical or economic importance, and those organisms that have the potential to provide insight into biodiversity change over time because they are most susceptible to global change. In discussing the future of collections-based systematics, researchers have highlighted the importance of updated monographic workflows, collaborative teams, and effective ways to educate and disseminate the results of monographs to the public and scientific community (e.g., Wen et al., 2015; Grace et al., 2021). Here, we discuss how improving recognition, support, and access can lead to greater inclusivity while promoting a more active, sustainable, and collaborative outlook for monographic research.